The Quick Overview of Snakebite Research in the Indonesian Language with the Open Knowledge Map - Dewi Yuniasih; Muhammad Agita Hutomo; Andika Ilham Rahmatullah (JURNAL IMPLEMENTA HUSADA, 2025)
The aim of this study was to provide a concise overview of existing research and publications related to snakebite in Indonesia, specifically those published in Indonesian-language journals. Using the Open Knowledge Map (OKM) tool, a mapping analysis and data visualization were conducted to identify research gaps and describe the current knowledge landscape. A search query was formulated in the Indonesian language (“Gigitan Ular”) to assess academic interest and publication trends. The search identified six thematic clusters associated with the keyword, comprising a total of 28 articles. After removing 8 duplicates, 20 unique articles were screened for relevance. Of these, 13 met the inclusion criteria, while 7 were excluded due to irrelevance—specifically, studies involving non-human subjects or conducted outside Indonesia (e.g., Malaysia). The thematic analysis revealed that published studies mostly focused on six key areas: compartment syndrome, pre-hospital snakebite management, education about snakebite, characteristics of snakebite patients, ethnomedicine for snakebite, and disseminated intravascular coagulation (DIC) following snakebite. These topics reflect a wide range of clinical, educational, and sociocultural dimensions of snakebite management in the Indonesian context. However, the findings also highlight that snakebite remains an under-researched topic in Indonesian-language scientific literature. One limitation of this study is that the OKM platform accommodates a limited number of indexed articles, which may restrict the comprehensiveness of the analysis. Nonetheless, this study offers a rapid and structured synthesis of snakebite-related literature in Indonesia and underscores the need for greater scholarly focus on this neglected public health issue.